Rheumatoid arthritis bone erosion volumes on CT and MRI: reliability and correlations with erosion scores on CT, MRI and radiography. Issue 10 (2nd July 2007) - Døhn, Uffe Møller; Ejbjerg, Bo J; Hasselquist, Maria; Narvestad, Eva; Court-Payen, Michel; Szkudlarek, Marcin; Møller, Jakob; Thomsen, Henrik S; Østergaard, Mikkel
Abstract : Objectives: To investigate intramodality and intermodality agreements of CT and MRI erosion volumes in metacarpophalangeal (MCP) joints in rheumatoid arthritis (RA), and to compare the volumes with erosion scores for CT, MRI and radiography. Methods: In total, 17 patients with RA and four healthy controls underwent unilateral CT, MRI and radiography of second to fifth MCP joints in one hand. Erosion volumes (using OSIRIS software) and scores were determined from CT, MRI and radiography (scores only). Results: CT, MRI and radiography detected 77, 62 and 12 erosions, respectively. On CT, the mean erosion volume was 26 mm 3 (median 10; range 0 to 248) and 30 mm 3 (18; 1 to 163) on MRI. Total erosion volumes (per patient/control) were 97 mm 3 (29; 0 to 485) on CT and 90 mm 3 (46; 0 to 389) on MRI. For volumes, Spearman correlation coefficients were 0.96 to 0.99 (CT vs CT), 0.95 to 0.98 (MRI vs MRI) and 0.64 to 0.89 (CT vs MRI), all p<0.01. MRI erosion volumes correlated with the Outcome Measures in Rheumatology Clinical Trials/Rheumatoid Arthritis Magnetic Resonance Imaging Score (OMERACT RAMRIS) erosion scores (0.91 to 0.99; p<0.01) and the Sharp/van der Heijde erosion score (0.49 to 0.63; p<0.01). Conclusion: Very high intramodality and high intermodality agreements of CT and MRI erosion volumes were found, encouraging further testing in longitudinal studies. A close correlation with CT and MRI erosion volumes supports the OMERACT RAMRIS erosion score as a valid measure of joint destruction in RA.